Make in the public sector or buy from the private sector? The regulation of administrative self-supply in Spain - Amoedo-Souto, Carlos Alberto (2021)
This paper draws up an overview on the current status of in-house providing techniques in Spain. The concept of administrative self-supply is provided in order to cover and explain the most common modes of fulfilling the needs of services, goods and utilities whitin the public sector. We discuss the “make or buy decisions”, according to the new public procurement Act (9/2017), and the rise of public markets apart from business markets. Finally, we put this subject under the light of the transnational debate about the need of improving performance of public sector as a tool for Werlfare State empowerment.